PEMBERIAN PIJAT AROMA TERAPI LAVENDER PADA KEJADIAN DISMINORRHEA REMAJA PUTRI - Frisca Desma Ayu Kusuma Wardani; Sally Joncicilia; Meiliana Meiliana (Jurnal Kesehatan, 2022)
Currently there are many dysmenorrhea sufferers who actually really need serious attention, so that the existing symptoms can be treated immediately. Non-pharmacological pain management that can be done for menstrual pain (dysmenorrhea). One of them is by using lavender aromatherapy. This study aims to determine the relationship between lavender aromatherapy massage and the incidence of dysmenorrhea in young women in Bengkalak Island Village, Teupah Selatan District, Simeulue Regency in 2019. This type of research is a quasi experiment, with the design used being one group pre-test post-test. Population In this study, there were 89 young women with a purposive sampling technique and the number of samples obtained was 30 respondents.